1996
DOI: 10.1055/s-2007-999013
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Activity of Argatroban in Experimental Thrombosis in the Rabbit

Abstract: Argatroban was evaluated in three models of thrombosis in the rabbit: the Wessler model (thromboplastin plus stasis of the left jugular vein), an arteriovenous shunt model, and a model of arterial thrombosis induced by endothelial and intimal damage of the left femoral artery. Calcium heparin was used as a comparator. Both substances inhibited thrombus formation in the Wessler model with ID50 values of 0.32 and 0.16 mg/kg intravenous bolus for argatroban and heparin respectively, with similar changes in thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…The mixed micellar formulation of argatroban was also active in the rabbit Wessler model when administered 30 min prior to thrombus induction with 50 and 73% inhibition of thrombus formation obtained after 1 and 2 mg/kg s. c. The choice of the administration time was based on the time course of the anticoagulant effect observed with mixed micellar argatroban in this species (15). We have previously shown that argatroban in the absence of mixed micelles is active in this model when given as an i. v. bolus 10 min prior to thrombus induction (10). This in itself is not surprising.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The mixed micellar formulation of argatroban was also active in the rabbit Wessler model when administered 30 min prior to thrombus induction with 50 and 73% inhibition of thrombus formation obtained after 1 and 2 mg/kg s. c. The choice of the administration time was based on the time course of the anticoagulant effect observed with mixed micellar argatroban in this species (15). We have previously shown that argatroban in the absence of mixed micelles is active in this model when given as an i. v. bolus 10 min prior to thrombus induction (10). This in itself is not surprising.…”
Section: Discussionsupporting
confidence: 55%
“…Argatroban ((2R,4R)4-methyl-{N 2 -[(3-methyl-1, 2, 3, 4, tetrahydro-8-quinolyl) sulphonyl]-L-arginyl}-2-piperidinecarboxylic acid monohydrate) is a synthetic thrombin inhibitor, which selectively inhibits the amidolytic activity of thrombin via an interaction with the active site (3,4). Argatroban is active against clot-associated thrombin (5,6), and has been shown to have antithrombotic activity in a wide variety of animal models of thrombosis when given as an intravenous infusion (7)(8)(9)(10)(11)(12). However, the solubility of argatroban in aqueous solvents (< 1 mg/ml) precludes its use for subcutaneous administration in the prevention of deep vein thrombosis due to the limitations of the volumes that can be administered by this route.…”
Section: Introductionmentioning
confidence: 99%
“…Rat venous stasis model Thrombus formation was induced in anesthetized rats ( n = 10 per dose group) as described previously, with minor modifications [8]. The abdominal vena cava was exposed and two loose sutures (8–10 mm apart) were placed below the left renal venous branch.…”
mentioning
confidence: 99%
“…Arteriovenous shunt model in rats and rabbits An arteriovenous (AV) shunt in anesthetized rats and rabbits was performed as described previously, with minor modifications [8–10]. The right common carotid artery and the left jugular vein were cannulated with two 100‐mm‐long, saline‐filled catheters.…”
mentioning
confidence: 99%
“…Argatroban ((2R,4R)4-methyl-{N 2 -[(3-methyl-1,2,3,4, tetrahydro-8-quinolyl) sulphonyl]-L-arginyl}-2-piperidinecarboxylic acid monohydrate) is a synthetic thrombin inhibitor, which selectively inhibits the amidolytic activity of thrombin via an interaction with the active site (5,6). Argatroban is active against clot-associated thrombin (7,8), and has been shown to have antithrombotic activity in a wide variety of animal models of thrombosis when given as an intravenous infusion (9)(10)(11)(12)(13)(14). However, the solubility of argatroban in aqueous solvents (1 mg/ml) precludes its use for sub-cutaneous administration in the prevention of deep vein thrombosis due to the limitations of the volumes that can be administered by this route.…”
Section: Introductionmentioning
confidence: 99%